Caminhar imagens: visualidades de São Paulo - Flavio Pinto Valle (2018)
The aim of this thesis is the elaboration of a theoretical methodological proposal of apprehension of the historicity of the urban processes in progress in a city based on the reading of its iconography, in particular, of its photographic images. For this, we present a conception of the city as a text that is woven through different sociocultural practices, to which specific modalities of reading the urban environment correspond. To understand the city as a text that is fabricated by the practices that are carried out in it is to understand it as much as the materiality where this text emerges and is inscribed, as well as the index of those practices that identify it and that reference it, and that both texts and practices, are signs that compose it in semiosis with others. In this perspective, if the texts are index of the practices of the citizens, then reading them is, in some measure, a way of practicing them. From this it follows that if walking is the most elementary way of practicing the city, then reading the texts of the city is, in some way, walking through them. Based on these conceptions of the city and the reading we propose the accomplishment of a methodological exercise that consists of writing our walk through the São Paulo iconography. A writing that is not limited to describing the places of this city that reveals itself to us through our reading, but which mainly narrates the movements that we carry out within the spaces crossed by our walk. Such a methodological operation presupposes the confrontation with other cities located in other times and in other spaces and that our walk / reading makes contemporaries. One of these cities is the Paris of the late nineteenth century, where the passage from the medieval village to the modern city was not only recorded, but was also guided by photography. Since the walk contains something that can not be explained, which can only be practiced, at first we will offer our reader a footpath through the city of São Paulo and then the associations we manufacture along the route for the purpose of to understand how the process of production of urban territory, mediated by real estate speculation, was captured and shown by the work of photographers who have worked or who still work in São Paulo.